Nuclear level lifetime measurements across varied ranges using the digital INGA at TIFR - Rudrajyoti Palit; Rajarshi Raut (AAPPS Bulletin)
Abstract This article highlights the significance of level lifetime measurements in nuclear structure studies that principally center on probing the myriad excitation phenomena exhibited by nuclei through evolving regimes of excitations in energy, angular momentum, and isospin. The same has been illustrated through discussions on some of the measurements undertaken using the Indian National Gamma Array (INGA) set up at the BARC-TIFR Pelletron LINAC Facility (PLF) in TIFR, Mumbai. The diverse physics that could be addressed in such endeavors provides the impetus to work towards developing better facilities for spectroscopic pursuits.